The Black Pill: New Technology and the Male Supremacy of Involuntarily Celibate Men. (December 2021) - Preston, Kayla; Halpin, Michael; Maguire, Finlay
Involuntary celibates, or "incels, " are people who identify themselves by their inability to establish sexual partnerships. In this article, we use analytic abduction to qualitatively analyze 9, 062 comments on a popular incel forum for heterosexual men that is characterized by extensive misogyny. Incels argue that emerging technologies reveal and compound the gender practices that produce involuntarily celibate men. First, incels argue that women's use of dating apps accelerates hypergamy. Second, incels suggest that highly desirable men use dating apps to partner with multiple women. Third, incels assert that subordinate men inflate women's egos and their "sexual marketplace value" through social media platforms. We argue that incels' focus on technology reinforces essentialist views on gender, buttresses male domination, dehumanizes women, and minimizes incels' own misogyny. We discuss findings in relation to theories of masculinity and social scientific research on the impacts of emerging technology.